US geopolitical codes and role of Persian gulf oil in US military intervention in the region (2001-2004) - Naji, Saeid (2012)
This thesis examines the role of the Persian Gulf oil as a geoeconomic factor in the US military intervention in the Persian region. This role is examined in relation to the US attempts to preserve its world leadership position and reconstruct a new geopolitical world order. This role is examined by analyzing US geopolitical codes. This examination focused on the US geopolitical code during the first term of the George W. Bush presidency between 2001 and 2004. A qualitative content analysis technique was used to analyze data in order to get an in-depth understanding of the US geopolitical code. In this respect, selected US presidential speeches and some official documents such as National Security Strategy and National Energy Policy, as well as the important relevant past studies were consulted and analyzed. Data analysis revealed a number of important findings. Firstly, there has always been a close connection between geopolitical codes of the United States and its world leadership position. The American geopolitical culture postulates the US as a “holy land” with the “chosen people”. Therefore, the country has a mission to spread and defend freedom, democracy and peace around the globe. After September 11, global terrorism came to be defined as the main threat to the civilized world and American values. To defend these values, Bush argued that there was therefore a need to reinforce US military might and its global actions as a world leader. Secondly, since the Second World War, the importance of the Persian Gulf region remained as prominent geopolitical assumption in defining the US geopolitical codes. The importance of this oil rich region as US vital interests has clearly been asserted in the various American doctrines during different periods. Based on US geopolitical codes, all threats to this vital area must be countered by force. In this respect, the Iraqi regime was defined as a serious threat to these regional interests. Iraq was also linked to terrorism and the proliferation of weapons of mass destruction. That consequently justified a pre-emptive war against Iraq to preserve US interests. Lastly, the US military intervention in Iraq would mean reinforcing the US presence in the region as well as controlling the richest oil area in the world. The geoeconomics of controlling oil would mean controlling the global economy and other great rival powers, which are the most important oil consumers as well. This would thus ensure the security of oil flow toward all industrial countries as well as preserving the interests of US friendly states. It would also portray the United States as a benevolent leader and increase its legitimacy, which had been declining since the early 1970s. And finally, it would help to impose the US global geopolitical code on other states in the reconstruction of the new geopolitical world order in order that the US world leadership would continue.